Delay in the criminal justice system in Pakistan : a criminal analysis - Ali, Sadaqut (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
There are numerous pieces of literature on the obligations to expedite justice to a common man. Unfortunately, what happens is, the courts themselves are guilty of inordinate delay. Delay in courts is a global concern as justice delayed is justice denied. Unlike other countries, the backlog in the criminal courts of Pakistan is increasing at an alarming pace. In countries using the common law system, the prevalent mode of resolving disputes continues to be adversarial, where a judge does not play an active role in investigation and prosecution as opposed to the inquisitorial system where a judge takes part in inquiry, investigation, and prosecution. This study has analyzed the causes of delay in the criminal justice system of Pakistan. As far as the delay is concerned, this study has examined and compared the criminal justice systems in common law countries in Pakistan and Malaysia, with the inquisitorial legal system in France. A qualitative research methodology has been conducted where apart from doctrinal research, a critical and comparative analysis is made by the researcher. Through analyzing each criminal justice system separately and comparatively, the shortcomings in the criminal justice system of Pakistan that contributed to the inordinate delay in the disposal of cases can be identified. Recommendations can then be provided to rectify those shortcomings hence ensuring the expeditious disposal of criminal cases. Besides, the adverse effects of inordinate delay to suspects, accused persons, victims, and witnesses are also discussed as their fates too are intertwined.